Synthesis and Studies on the Anticonvulsant Activity of 5-alkoxy-[1,2,4]triazolo[4,3-a]pyridine Derivatives - Guan, L.-P.; Zhang, R.-P.; Sun, Y.; Chang, Y.; Sui, X. (Arzneimittelforschung, 2012)
In this study, a series of new 5-alkoxy-[1,2,4]triazolo[4,3-a]pyridine derivatives was synthesized and their anticonvulsant activity and neurotoxicity was evaluated with the maximal electroshock and rotarod tests, respectively. The most promising compounds, 3p (5-(4-chlorophenoxy)-[1,2,4]triazolo[4,3-a]pyridine) and 3r (5-(4-bromophenoxy)-[1,2,4]triazolo[4,3-a]pyridine), showed a median effective dose of 13.2 and 15.8 mg/kg and had a protective index value of 4.8 and 6.9, respectively. For exploring the putative mechanism of action, compounds 3n, 3p and 3r were tested in chemically induced models.
Keywords: [1,2,4]triazolo[4,3-a]pyridine; synthesis; anticonvulsant activity; chemically induced model